2016
DOI: 10.1097/md.0000000000005535
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pancreatic cystic neoplasms in an asymptomatic healthy population of 21,745 individuals

Abstract: Although incidental pancreatic cystic neoplasms are being diagnosed with increasing frequency, little is known about the accurate prevalence of pancreatic cysts in the general population. The aims of this study were to evaluate the crude prevalence rate of pancreatic cystic neoplasms in asymptomatic healthy adults, and calculate the age- and sex-adjusted nationwide prevalence rate.A total of 21,745 asymptomatic individuals who underwent abdominal computed tomography (CT) as a health screening examination were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 38 publications
6
91
2
5
Order By: Relevance
“…The exact prevalence of the different PCN is not known. Studies which assessed the prevalence rate of asymptomatic PCN reported a prevalence of 2.2-2.6% with computed tomography (CT) [10,11,12,13] and a prevalence of 14-45% with magnetic resonance imaging (MRI) [13,14,15]. This risk increases with age [10,11,12].…”
Section: Epidemiologymentioning
confidence: 99%
“…The exact prevalence of the different PCN is not known. Studies which assessed the prevalence rate of asymptomatic PCN reported a prevalence of 2.2-2.6% with computed tomography (CT) [10,11,12,13] and a prevalence of 14-45% with magnetic resonance imaging (MRI) [13,14,15]. This risk increases with age [10,11,12].…”
Section: Epidemiologymentioning
confidence: 99%
“…Radiographic studies using either computed tomography or magnetic resonance imaging have demonstrated that pancreatic cystic lesions can be found incidentally in ~2.5% of patients undergoing abdominal imaging (1)(2)(3). Although the vast majority of these small lesions are not currently sampled endoscopically by endoscopic ultrasound fi ne needle aspiration, a number of prior surgical series suggest that generally-in the absence of a history of acute or chronic pancreatitis-the majority of these cystic lesions are mucinous neoplasms primarily branch duct intraductal papillary mucinous neoplasms (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…This tumor remains one of the most lethal malignant neoplasms in western countries and is among the leading causes of cancer mortality, despite its relatively low incidence [2, 3]. Recent reports describe an increase in the incidence of asymptomatic pancreatic nodules, both solid and cystic, that are incidentally discovered due to the widespread use of imaging studies for different medical conditions [4, 5]. However, this earlier detection has so far not translated into better survival rates, for still more than 50% of patients are diagnosed at metastatic nonresectable stages [6] and are not amenable to cure, despite recent advances in therapy.…”
Section: Introductionmentioning
confidence: 99%